An active PID-based inertial control of a doubly-fed induction generator - Ahmad, Thelfa; Littler, Tim; Naeem, Wasif (2016 27th Irish Signals and Systems Conference (ISSC), 2016)
The increasing level of wind power integration using doubly fed induction generators (DFIGs) has implications for local frequency support as a consequence of decoupling between DFIG rotor speed and grid frequency. To ensure reliable and stable power system operation with DFIG integration, supplementary inertial control strategies are required. Conventional inertial control algorithms which use the rate of change of frequency (RoCoF) and frequency deviation loops (droop loop) require great effort to determine appropriate gains suitable for all power grid and wind speeds. In this paper, the influence of supplementary inertial control loop parameters on the inertial response and power system frequency are analysed. An active control strategy is proposed for frequency regulation using variable gains in the frequency deviation loop for the inertial controller. The variable gain control approach is shown to actively respond to system changes to improve the performance. The controller is compared with the widely used PID method. The proposed method is shown to enhance the frequency nadir and guarantee steady DFIG operation.